UJI ANGKA LEMPENG TOTAL DAN ANGKA KAPANG KHAMIR PADA Pleurotus ostreatus DAN Ganoderma lucidum - Putri, Amanda Nabila; Setiawati, Asti Anwar; Masruuroh, Dina; Absani, Afriyanti Rifqi; Surahmaida, Surahmaida; Lestari, Kinanti Ayu Puji; Yuliarni, Floreta Fiska (Biospecies, 2025)
Mushrooms are a source of antioxidants. Mushrooms can be processed into various products. Both raw materials and finished products from mushrooms must comply with established standards. The aim of this research was to determine the total plate count and total fungal count in Ganoderma lucidum and Pleurotus ostreatus samples. The method used is the Total Plate Count (TPC) and Total Fungal Count (TFC). The TPC value in G. lucidum was 6.4 x 106 CFU/g and TFC was 3.9 x 105 CFU/g. This value exceeds the BPOM maximum standard for tea products or herbal brews. The TPC value in P. ostreatus was 1.2 x 105 CFU/g and TFC was 4.9 x 105 CFU/g. The TPC value for P. ostreatus is less than the maximum standard set by BPOM, while the TFC value exceeds the maximum standard for powder or mixture of soup and broth. The conclusion of this research is that the TPC and TFC in the G. lucidum and P. ostreatus samples exceed the standards set by BPOM No. 13 of 2019 except for the TPC in the P. ostreatus sample.